Understanding Osaka mutation polymorphic Aβ fibril response to static and oscillating electric fields: insights from computational modeling - Mukhriddin Makhkamov; Artyom Baev; Erkin Kurganov; Jamoliddin Razzokov (Scientific Reports, 2024)
Abstract Alzheimer’s disease (AD) is a prevalent neurodegenerative disorder, impacting millions of individuals worldwide. Among its defining characteristics is the accumulation of senile plaques within the brain’s gray matter, formed through the self-assembly of misfolded proteins contributing to the progressive symptoms of AD. This study investigates a polymorphic Aβ fibril under static and oscillating electric fields using molecular dynamics simulation. Specifically, we utilized a polymorphic fibrillar complex composed of two intertwined pentamer-strands of the Aβ1–40 peptide with the Osaka mutation (E22Δ), known for its toxicity and stable structure. Our findings demonstrate that a 0.3 and 0.4 V/nm electric field combined with a 0.20 GHz frequency effectively disrupts the polymorphic conformation of Aβ fibrils. Furthermore, we elucidate the molecular mechanisms underlying this disruption, providing insights into the potential therapeutic use of oscillating electric fields for AD. This research offers valuable insights into novel therapeutic approaches for combating AD pathology.